Designing collaborative governance: Insights from the drought contingency planning process for the lower Colorado River basin. Issue 91 (January 2019) - Sullivan, Abigail; White, Dave D.; Hanemann, Michael
Highlights: The Colorado River, a vital resource, is facing increasing water shortages. We systematically analyze a policy process intended to address water shortage. We find multiple barriers have hindered efforts to collaboratively address shortage. Analyzing power dynamics among stakeholders involved is key to increasing success. Our approach using a public dataset can be adapted to explore other systems. Abstract: Agriculture, environment, industry, and millions of households in the western US and northern Mexico depend on the Colorado River, which is facing increasing water shortages due to climate change and rising demand. Collaborative governance will likely be key to solving allocation issues and achieving sustainable water use but has recently faced multiple challenges. This research integrates concepts from institutional, adaptive governance, and bargaining theories to analyze barriers and facilitators to collaborative governance in the drought contingency plan (DCP) process for the lower Colorado River basin from an Arizona stakeholder's perspective. The DCP is ultimately an effort to create a set of rules to prevent and address shortages in the basin. Through a content analysis of public meetings of the Central Arizona Project's governing board, we find a collective DCP or future related policy may be possible. But barriers to collaborative governance have intensified over time, hindering the process and making an agreement increasingly unlikely. The process is a perfect example of the interplay between rules and norms, and the issues that arise when norms underlying rules are interpreted differently. Our analysis provides insights for the design of collaborative water governance, including that conducting an analysis of power dynamics among the stakeholders would advance the DCP process. We ultimately argue that the Colorado River basin would benefit from a transition towards adaptive governance, and that our recommendations to improve collaboration are an important initial step. Additionally, our results reveal areas that require more empirical research, including understanding how to prepare for policy windows, rapid trust building among stakeholders, and theory building related to equity and marginalization in collaborative governance processes.